2009
DOI: 10.1051/medsci/20092511921
|View full text |Cite
|
Sign up to set email alerts
|

Entérovirus non poliomyélitiques et pathologies respiratoires

Abstract: Des agents infectieux communs en pathologie humaineLes entérovirus (Picornaviridae) sont très communs en médecine humaine et sont responsables d'environ un milliard d'infections chaque année dans le monde [1,2]. Le genre entérovirus de la famille des Picornaviridae est constitué de petits virus non enveloppés à ARN simple brin de polarité positive [2]. Il comprend actuellement 108 sérotypes pathogènes pour l'homme, répartis en 4 espèces notées de A à D. Leur classification est en permanente évolution grâce à l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
2
6
0
2
Order By: Relevance
“…These infections have been detected in all months of the year except for June. It has been reported that coronavirus infections peaks mostly in winter months without a significant difference in seasonality or origin (obtained from community or hospital) between the four subtypes (33,34). In conformity with previous studies, our study found that coronaviruses peak in winter months.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These infections have been detected in all months of the year except for June. It has been reported that coronavirus infections peaks mostly in winter months without a significant difference in seasonality or origin (obtained from community or hospital) between the four subtypes (33,34). In conformity with previous studies, our study found that coronaviruses peak in winter months.…”
Section: Discussionsupporting
confidence: 92%
“…Enteroviruses peak in late summer and autumn months and seen in winter in temperate climates. Jacques et al (34) have conducted a research in between French children and reported that 47% of enterovirus infections occur in spring and autumn months (35,36). In our study, nearly all enterovirus infections were detected in winter.…”
Section: Discussionsupporting
confidence: 55%
“…Enterovirus is a well-known pathogen in upperairway infections. However, several reports have also proposed its involvement in the development of LRTI, pneumonia included, in immunocompetent infants and adults Andreoletti et al 2009).…”
Section: Enterovirusmentioning
confidence: 99%
“…Bu enfeksiyonlar, haziran ayı haricinde yılın tüm aylarında tespit edildi. Koronavirüs enfeksiyonlarının, kış aylarında dört alt tip arasında mevsimsellik ve köken açısından (topluluk veya hastanede elde edilen) anlamlı bir fark olmadan en çok kış mevsiminde zirve yaptığı bildirilmiştir (33,34). Çalışmamızda daha önceki çalışmalarla uyumlu koronavirüslerin en sık kış aylarında zirve yaptığı belirlenmiştir.…”
Section: Discussionunclassified
“…Tokak ve ark. Enterovirüsler endemik olarak meydana gelen enfeksiyonlar ılıman iklimlerde geç yaz ve erken sonbaharda pik yaparak kış aylarında görülmektedir. Jacques ve arkadaşları Fransız çocuklar arasında yaptıkları çalışmada, enterovirüs enfeksiyonlarının %47'sinin sonbahar ve ilkbahar aylarında meydana geldiğini bildirmişlerdir (34)(35)(36). Çalışmamızda enterovirüslerin tamamına yakını kış mevsiminde saptanmıştır.…”
Section: Discussionunclassified